We need to solve the next system of equations:
![\begin{gathered} 5x+6y+3z=-1 \\ 3x+5y+4z=-5 \\ -x-2y-2z=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uli0cim4kb42qwt5psegeplsreoapf2ev5.png)
Lets pair equations to eliminate one variable:
![\begin{gathered} 5x+6y+3z=-1 \\ 3x+5y+4z=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mwthzbstcj4ecwnhadfj7q18bhvs68rzpg.png)
Multiply the first equation by -3 and the second equation by 5:
![\begin{gathered} -3(5x+6y+3z=-1) \\ 5(3x+5y+4z=-5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y5teegg1ot36v6c7lgop4z0p74udx4lq7p.png)
Then, add equations:
![\begin{gathered} -15x-18y-9z=3 \\ 15x+25y+20z=-25 \\ ------------ \\ 0+(-18y+25y)+(-9z+20z)=(3-25) \\ ----------------------- \\ 7y+11z=22 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rqrxlsnxe3mrv8v061zbvmadoow2i5jxv3.png)
The second pair :
![\begin{gathered} 3x+5y+4z=-5 \\ -x-2y-2z=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u9udnimm01ob45ya01jw7m2uc4ci5zbgdh.png)
Multiply the first equation by 1 and the second equation by 3:
![\begin{gathered} 1(3x+5y+4z=-5) \\ 3(-x-2y-2z=5) \\ \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b0mbon00513oqi64nfbs2b49cfwhn0m372.png)
Add both equations:
![\begin{gathered} 3x+5y+4z=-5 \\ -3x-6y-6z=15 \\ ------------- \\ 0+(5y-6y)+(4z-6z)=-5+15 \\ ------------------------ \\ -y-2z=10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vzdsbmzce2bzhql2hskf67fzpil9ijld07.png)
Solve the new system:
![\begin{gathered} 7y+11z=22 \\ -y-2z=10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6k6wmynrxcuctpvg0bkbwu0l8dlmq3ufe9.png)
Multiply the first equation by 1 and the second equation by 7:
![\begin{gathered} 1(7y+11z=22) \\ 7(-y-2z=10) \\ \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qkx28uwjakph3mjzmqo08ps36bsv7c4z5v.png)
Add both equations:
![\begin{gathered} 7y+11z=22 \\ -7y-14z=70 \\ ------------- \\ 0+(11z-14z)=-22+70 \\ ---------------- \\ -3z=48 \\ z=-16 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/aefr1to7qi22m7o0522bw11syr7c3qinkd.png)
Replace the z value on one equation:
![-y-2(-16)=10](https://img.qammunity.org/2023/formulas/mathematics/college/ig5ue9dx7egl0d5m6ad9odgp7xxb0k8xj9.png)
Solve for y:
![\begin{gathered} -y+32=10 \\ \\ -y=10-33 \\ y=22 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hikx439fpn3b6yvza30ojsvg1buw6lixl5.png)
Finally, replace the y value and the z value:
![\begin{gathered} -x-2y-2z=5 \\ -x-2(22)-2(-16)=5 \\ -x-44+32=5 \\ -x-12=5 \\ -x=5+12 \\ x=-17 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/toe0dpwnvy5mc829kgg4c0e9wosgbv69k5.png)
Hence, the result for the variables are:
x=-17
y=22
z=-16